PENGARUH FRAUD PENTAGON DALAM PENDETEKSIAN FRAUDULENT FINANCIAL REPORTING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Rahmani, Suci; Amin, Muhammad Nuryatno (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2021)
AbstractThenmain objectivemof this studynis to analyzenthe factorsnof fraudulent financialnreporting withnpentagon fraudnanalysis. Thisnresearch usesnfive independentmvariables whichmis pressuremwith financialmtarget proxy, opportunityiwith proxynof ineffectiveimonitoring, rationalizationiwith change in auditornproxy, competencenwith proxy changenof director, andlarrogance with proxylfrequent numberlof CEO's picture. Whilelthe dependentpvariable is fraudulentlfinanciallreporting. Thisnresearch usespsecondary datapthat islfinancial reportpand annual report. Thelsample ofpthis studypare 41osamples ofnfinancialpcompanies listednin thenIndonesianStock Exchange (BEI) duringnthei2015 - 2017 period. Samplingntechniquenused ismpurposivensamplingomethod. Thepmethod of analysis innthis studyouses logistic regression no analysisi method. The resultskof thisnresearch showsjthat themineffective monitoring variablenhas aipositive significantoinfluence ofifraudulent financial reporting, meanwhile financialntargets has apnegative significantninfluence. Changeoin auditor,change of director, and frequent number of CEO'sjpicturemhas no influence of fraudulentnfinancial reporting.Keywords: Fraud; Fraudulent Financial Reporting; Fraud Pentagon